The Flouting of Maxim in the Se7en Movie Script - Shafira Annisa Rizky (ESENSI LINGUA, 2023)
This research focused on analyzing flouting of maxims that were flouted by the characters in the Se7en movie script and the motivation of the characters flouted the maxims. This research used qualitative research method. The data of the research were in the form of utterances that contained flouting of maxim. The data were collected by downloading the movie and the script, watching the movie, and collecting the data from the script. The data analysis was conducted by organizing the data into narration, analyzing the data, and drawing the conclusion. The results of the research showed what types of maxims were flouted in the movie and what motivation that led the characters to flout the maxims. There are four flouting of maxims in the Se7en movie script; they are maxim of quantity, maxim of quality, maxim of relevance, and maxim of manner.